We Can Unify Quantum Mechanics And Gravity Only By ToE i.e MIND - Das, Vijay Mohan (Archives of Business Research, 2015)
A Theory of Everything would unify all the fundamental interactions of nature: gravitation, strong interaction, weak interaction, and electromagnetism. Because the weak interaction can transform elementary particles from one kind into another, the ToE should also yield a deep understanding of the various different kinds of possible particles. The usual assumed path of theories is given in the following graph, where each unification step leads one level up In Unification physics where four fundamental forces are tried to unify . It means Four natural forces which are mediated by four particles ( photon, vector boson , gluons and gravitons) are created from one particle . It is called super unification. GUT means three forces ( Photon, vector bosons, and GLUON ) could be unified as these are made up of one type of fundamental particle called energy basic building blocks .